Ngugi wa Thiong'o. Matigari. Rafael Segovia A., trad. del inglés. México: El Colegio de México, 2005. 196 pp. - Villalobos, J. Waldo; Segovia, Rafael (Estudios de Asia y África, 2007)
Ngugi wa Thiong'o. Matigari. Rafael Segovia A., trad. del inglés. México: El Colegio de México, 2005. 196 pp.